Maternal and fetal outcome in oligohydramnios: study from a tertiary care hospital, Ahmedabad, India - Ghosh, Runoo; Oza, Heena; Padhiyar, Bhakti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Most severe and frequent complication of pregnancy is Oligohydramnios and the incidence of this is observed to be about 1-5 % of total pregnancies. Objective of present study was to find the maternal and perinatal outcome, etiology associated with oligohydramnios at tertiary care hospital. Methods: This prospective study was done among 55 patients with gestational age from 30-40wks with Oligohydramnios AFI<5cms with intact membranes were analysed for perinatal outcomes admitted at department of obstetrics and Gynecology in B.J. Medical college, Ahmedabad during July 2008 to July 2010. Results: 65.5% participants were belonged to 20 to 25 age group and 35.5% participants were Primigravida. Mean age was 23.9±3.3 years and mean gestation age was 36.9 week. Almost 72.2% were in 34 to 37 weeks of gestational age. Study found FMC <10 in 56.4% of participants. Forty percent participants have AFI 4 and 27.3% have AFI 5. 47.3% delivery was done by vaginal route. 5.5% baby was still birth and prematurity were the most common cause of still birth. Around 71% babies were low birth weight and congenital anomalies were present in 7.3% babies. APGAR score measured <7 at 1 minute was in 65.4% and <7 at 5 minutes was in 43.6% babies. Conclusions: Oligohydramnios in obstetrics is a frequent occurrence and it points towards intensive surveillance and proper ante-natal and post-natal care. Due to high perinatal morbidity and mortality, the incidence of LSCS increases. However, vaginal delivery has similar outcome, but strict vigilance in labor is mandatory.